'Had on When She Went Away . . .': Expanding the Usefulness of Garment Data in American Runaway Advertisements 1750-90 through Database Analysis. - Fifield, Rebecca (Textile History, 2011)
Newspaper runaway advertisements are one of the best sources of information on American women's working-class dress, but have only been minimally analysed in quantity. This article presents a project in which the notices of 900 women's elopements and their 5,600 garments have been catalogued in a relational database to provide greater access to garment data in runaway advertisements, including textile use, colour and patterning information. Data about the women, including physical characteristics, geographical location and ethnicity are linked to the garment data to allow contextual searches. Select initial investigations into preconceived notions of women's working-class clothing during this period are included to demonstrate future research directions based on this approach.